Observed Relationships Between Cloud Droplet Effective Radius and Biogenic Gas Concentrations in Summertime Marine Stratocumulus Over the Eastern North Atlantic. Issue 2 (18th February 2022) - Miller, Mark A.; Mages, Zackary; Zheng, Qiuxuan; Trabachino, Lynne; Russell, Lynn M.; Shilling, John E.; Zawadowicz, Maria A.
Abstract: Biogenic gases are a prominent component of the summertime marine boundary layer (MBL) over the Eastern North Atlantic. One of these gases, dimethyl sulfide (DMS), can produce sulfate cloud condensation nuclei (CCN) that, in theory, can brighten clouds through photolysis, and produces a reaction product, methane sulfonic acid (MSA). It is also possible that DMS can interact with sea‐salt or other marine aerosols changing their CCN activation spectrum, which could also modify cloud microphysical structure. Data collected aboard the G1 aircraft during the Aerosol Cloud Experiment Eastern North Atlantic (ACE‐ENA) in well‐mixed and decoupled marine boundary layers (MBLs) were used to examine relationships between the cloud droplet effective radii, r e r_e, and the concentrations of DMS and MSA in constant cloud liquid water content (LWC) bins. A weak but statistically significant negative correlation was observed between CCN concentration and r e r_e in most LWC bins, regardless of the source of the CCN, while a weak but statistically significant positive correlation between r e r_e and DMS was observed. No correlation between the cloud droplet number concentration and DMS was found. The presence of MSA indicated that DMS‐to‐sulfate photolysis was likely occurring, but data sparsity prevented a statistically significant conclusion regarding the relationship between MSA and r e r_e . Data sparsity in decoupled conditions also prevented statistically significant conclusions. To properly address biogenic gas impacts on cloud microphysics, it is recommended that aircraft data be supplemented by long‐term biogenic gas measurements at the surface in marine locations with appropriate remote and in‐situ cloud sensing capabilities, and the analysis limited to well‐mixed MBL's. Plain Language Summary: Biological processes in the ocean produce gases that enter the lower marine atmosphere. One of these gases, dimethyl sulfide (DMS), can generate small aerosols known as cloud condensation nuclei that can potentially impact cloud properties. The processes through which DMS may interact with clouds are still relatively unknown. This study uses novel aircraft measurements to investigate these processes over the Eastern North Atlantic Ocean. These data show minimal relationships between DMS and cloud properties, but the limitations of the data set suggest a new data collection procedure might have better success. Key Points: Three well‐mixed stratocumulus layers exhibited weak but statistically significant positive correlations between dimethyl sulfide (DMS) concentration and droplet effective radii, r e r_e Three well‐mixed stratocumulus layers exhibit weak but statistically significant negative correlations between the concentration of cloud condensation nuclei (CCN) and r e r_e Data sparsity prevented any statistically significant conclusion regarding the correlation between methane sulfonic acid (MSA) and r e r_e